SGLT-2 inhibitors and prevention of contrast-induced nephropathy in patients with diabetes undergoing coronary angiography and percutaneous coronary interventions: systematic review and meta-analysis - Meregildo-Rodriguez, Edinson Dante; Asmat-Rubio, Martha Genara; Vásquez-Tirado, Gustavo Adolfo (Frontiers in Endocrinology, 2023)
SGLT2 inhibitors (SGLT2Is) have demonstrated cardioprotective and nephroprotective effects in patients with and without diabetes. Recent studies suggest that SGLT2Is may reduce the risk of contrast-induced nephropathy (CIN) in patients with diabetes undergoing coronary arteriography (CAG) or percutaneous coronary interventions (PCI). However, the evidence is still inconclusive. We aimed to systematically review the evidence regarding the potential nephroprotective role of SGLT2Is in preventing CIN in this population. We searched for studies in six databases published up to September 30, 2023, following a PECO/PICO strategy. Initially, we meta-analyzed five studies, but due to several reasons, mainly methodological concerns, we excluded one RCT. In our final meta-analysis, we included four observational studies. This meta-analysis comprised 2,572 patients with diabetes undergoing CAG or PCI, 512 patients treated with SGLT2Is, and 289 events of CIN. This is the first meta-analysis demonstrating that SGLT2Is may reduce the risk of developing CIN by up to 63% (RR 0.37; 95% CI 0.24-0.58) in patients with diabetes undergoing CAG or PCI, compared to not using SGLT2Is. Statistical heterogeneity was not significant (I 2 = 0%, p = 0.91). We assessed the certainty of the evidence of this systematic review and meta-analysis, according to the GRADE criteria, as moderate. In conclusion, SGLT2Is significantly reduce the risk of CIN by up to 63% in patients with diabetes undergoing CAG or PCI. Clinical trials are needed; several are already underway, which could confirm our findings and investigate other unresolved issues, such as the optimal dose, type, and duration of SGLT2 inhibitor therapy to prevent CIN.